One‐stage double free flap arteriovenous loop reconstruction of a massive abdominothoracic defect following necrotizing fasciitis: A case report. Issue 8 (21st October 2020) - Falkner, Florian; Thomas, Benjamin; Hundeshagen, Gabriel; Wittenberg, Gerhard; Bliesener, Björn; Bigdeli, Amir K.; Kneser, Ulrich
Abstract: We report the case of a 67‐year old male with necrotizing fasciitis after injection of the glenohumeral joint. After extensive debridement a massive defect from the left hip joint to the left upper arm, exposing ribs, scapula, axillary vessels and brachial plexus (45 × 40 cm) was present. Reconstruction was performed with a conjoined right myocutaneous tensor fasciae lata/vastus lateralis flap and a left myocutaneous vastus lateralis flap in combination with an arteriovenous loop originating from the axillary vessels using the greater saphenous vein. Revisional surgeries were necessary including ribs resection and flap re‐advancements. Due to multiorganic failure invasive ventilation, renal replacement‐ and extensive transfusion therapy was required. After 241 days the patient was discharged for rehabilitation. At the 12 months follow‐up wounds were sufficiently closed without the need for further intervention. This case illustrates that immediate diagnosis followed by an aggressive multidisciplinary treatment approach is crucial for the patient survival.